2014
DOI: 10.5604/20831862.1134558
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of whole body vibration on isometric strength, squat jump, and flexibility in well-trained combat athletes

Abstract: The purpose of this study was to investigate the effect of whole body vibration (WBV) training on maximal strength, squat jump, and flexibility of well-trained combat athletes. Twelve female and 8 male combat athletes (age: 22.8 ± 3.1 years, mass: 65.4 ± 10.7 kg, height: 168.8 ± 8.8 cm, training experience: 11.6 ± 4.7 years, training volume: 9.3 ± 2.8 hours/week) participated in this study. The study consisted of three sessions separated by 48 hours. The first session was conducted for familiarization. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
1
22
0
2
Order By: Relevance
“…WBV can potentiate handgrip performance, according to Kurt et al (2015). The results revealed a significant interaction of pre-post × intervention for the handgrip test, indicating a significant performance increase of moderate effect after WBV intervention.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…WBV can potentiate handgrip performance, according to Kurt et al (2015). The results revealed a significant interaction of pre-post × intervention for the handgrip test, indicating a significant performance increase of moderate effect after WBV intervention.…”
Section: Resultsmentioning
confidence: 75%
“…Studies have also described important effects of vibration exposure on upper body muscular activity, as an increase in skeletal muscle activity in the arms (Marín et al, 2015;Marín et al, 2011;Marín et al, 2013) and on the handgrip strength (Giminiani et al, 2014;Kurt et al, 2015) .…”
Section: Introductionmentioning
confidence: 99%
“…Grip tests were performed at standing position, with the shoulder adducted and neutrally rotated, and the elbow in full extension (Saha, 2014). The peak isometric force generated was quantified by multiplying the maximal measurement detected by the dynamometer by 9.81 m•s−2 (gravitational constant) in order to convert kilograms into Newtons (Kurt & Pekünlü, 2015).…”
Section: Participantsmentioning
confidence: 99%
“…A previous study compared the difference in electromyographic muscle activity between a group of healthy adults taking both isometric exercise and WBV on a vertical vibrating platform (a synchronous device) and another group taking the isometric exercise only, and reported that the former showed the most significant improvement in hand grasp strength (Dallas et al, 2013;Kurt & Pekünlü, 2015) . applied a vertical vibrating platform to athletes in a squat position of isolated and isometric contractions, and reported a significant improvement in the squat jump in contrast to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-Body Vibration (WBV) has been extensively investigated as a widely used training tool (Kurt & Pekünlü, 2015). A WBV device delivers vibration to the whole body on a synchronous vibration platform or side alternating vibration platform (Cardinale & Wakeling, 2005;Rauch et al, 2010).…”
Section: Introductionmentioning
confidence: 99%